Digitalisasi Manajemen Keuangan Lembaga Pembelajaran Al-Qur’an Pada TPQ Al-Ma’ruf Desa Jawik Kec. Tambakrejo Kab. Bojonegoro - Putri Wahyuni; Novie Andriani Zakariya; Airlangga Bramayudha (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2025)
This study aims to describe the process of digitalizing financial management at TPQ Al-Ma’ruf, Jawik Village, Tambakrejo District, Bojonegoro. The digitalization of financial systems in Islamic educational institutions is an important step to improve efficiency, transparency, and accountability in managing operational funds. This research uses a qualitative descriptive approach with interviews as the primary data collection technique. The interviews were conducted with the head and treasurer of TPQ Al-Ma’ruf to understand the implementation of digital financial recording using Microsoft Excel. The results show that the digitalization process simplifies financial reporting, reduces errors, and increases trust among parents and donors. Although there are still limitations in terms of training and system development, the adoption of digital recording tools has proven effective in supporting financial transparency. This study highlights the importance of digital literacy for Islamic educational institutions in facing technological progress